The protective effect of mushroom consumption on depressive symptoms in Korean population - Sung Keun Park; Chang-Mo Oh; Jae-Hong Ryoo; Ju Young Jung (Scientific Reports, 2022)
Abstract Mushrooms are nutraceutical food with health benefit. However, available data is still limited in identifying the effect of mushrooms consumption on depressive symptoms. In a cohort of 87,822 Korean, we longitudinally assessed the risk of depressive symptoms according to mushrooms consumption. Study participants were categorized into 5 groups by the frequency of one serving size of mushrooms (30 g) as follows: rare/never, < 1/month, 1/month–1/week, 1–3/week, ≥ 3/week. The development of depressive symptoms was determined in Center for epidemiological studies-depression scale ≥ 16. Cox proportional hazards model was used to calculate adjusted hazard ratio (HR) and 95% confidence intervals (CI) for depressive symptoms (adjusted HR [95% CI]). Subgroup analysis was performed for gender and age. Compared with group with rare/never consumption, groups with mushrooms consumption ≥ one serving size/month had the significantly decreased levels in adjusted HR and 95% CI for depressive symptoms (rare/never consumption: reference, < 1/month: 0.92 [0.83–1.02], 1/month–1/week: 0.88 [0.83–0.94], 1–3/week: 0.88 [0.82–0.94], ≥ 3/week: 0.86 [0.80–0.93]). This association was similarly observed in both gender and age subgroup analyses. However, women and participants ≥ age of 40 showed the more prominent association than men and participants < age of 40.